Development of an order processing system using Google Sheets and Appsheet for a Malaysian automotive SME factory warehouse / Mohamad Khairi Hassan, Mohd Hazri Mohd Rusli and Noor Azlina Mohd Salleh - Hassan, Mohamad Khairi; Mohd Rusli, Mohd Hazri; Mohd Salleh, Noor Azlina (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
The automotive industries in Malaysia have grown well and developed many suppliers in their supply chain including Small Medium Enterprise (SME). The order handling process at a supplier's factory has become one of the most critical areas in the supply chain. Adaptation to technology such as IoT enables the automotive supplier to better manage their customer orders and avoid mistakes that affect the supply chain. In order to improve the order processing activities, a study has focused on developing a mobile device application using Google Appsheet and Google Sheets as a cost-effective system for managing supply orders. A study was conducted in one of Malaysian SME automotive companies, which manages the orders manually by using a log book with a lot of recording and redundant work. By using Google Sheets, all the information and data involved in order processing activities is imported and digitized. Then, a mobile application is created using Appsheet so that the ordering activities and processing can be completed on a mobile device. All information gathered by the mobile app (Google Appsheet) is immediately saved in Google Sheets on an Excel-based database, allowing for further data analysis. The research conducted has managed to integrate these two applications into a system for Malaysia's SME factory to manage the ordering activities in the automotive supply chain. This system enables the user to shorten their order processing time since data is captured in real time and mistakes due to manual error can be avoided.